2001
DOI: 10.1161/hq1101.098232
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Complex Formation of Oxidized α 1 -Antitrypsin and LDL

Abstract: Abstract-An inactivated form of ␣ 1 -antitrypsin (AT) and LDL coelutes in gel permeation chromatography. To characterize and to quantify the amount of this fraction of AT, a monoclonal antibody was established against chloramine T-oxidized AT and named OxAT-4. OxAT-4 recognized the oxidatively modified AT, including hexylaldehyde-or 4-hydroxy-2-nonenal-modified AT, but neither normal active AT nor trypsin/AT complex. Comigration of apoB and oxidized AT was demonstrated by Western blotting analysis of AT-LDL by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 37 publications
(38 reference statements)
1
43
0
Order By: Relevance
“…SAA-LDL is a complex molecule generated through the oxidative interaction of SAA with lipoproteins, in the context of intravascular inflammation. 21,22 Accumulated oxLDL, which is easily taken up by macrophages through damaged endothelial cells, has a key role in the initiation and progression of inflammation and atherosclerosis. 18,19,24 Indeed, elevated oxLDL blood levels reflect the pathologic condition of the vessel wall, endothelial dysfunction and coronary plaque instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SAA-LDL is a complex molecule generated through the oxidative interaction of SAA with lipoproteins, in the context of intravascular inflammation. 21,22 Accumulated oxLDL, which is easily taken up by macrophages through damaged endothelial cells, has a key role in the initiation and progression of inflammation and atherosclerosis. 18,19,24 Indeed, elevated oxLDL blood levels reflect the pathologic condition of the vessel wall, endothelial dysfunction and coronary plaque instability.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 A sandwich enzyme-linked immunosorbent assay was used to determine the serum SAA-LDL level. 21,22 Intra-assay variations in low and high concentrations were 2.6 and 4.7%, respectively, whereas inter-assay variations in low and high concentrations were 5.0 and 6.7%, respectively. 21 …”
Section: Data Collection and Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, biological activities of A1AT can be modified due to interactions with lipid moieties, in which A1AT was found in association with cell membrane lipid rafts (19,20) and was detected in complexes with low-density lipoproteins (LDLs) and high-density lipoproteins (HDLs). (21,22) The binding of A1AT to HDL augments its protective effect in a mouse model of elastase-induced pulmonary emphysema. (22) We recently reported that A1AT purified from human plasma binds polyunsaturated fatty acids (FAs) like α-linoleic and oleic acid, and that only FA-bound forms of A1AT increase the expression and release of ANGPTL4 in human bloodadherent monocytic cells and in primary human lung microvascular endothelial cells.…”
Section: Caspase-1 Inhibition Assaymentioning
confidence: 99%
“…OxyA1AT has a potential clinical significance in atherogenesis. Mashiba et al (Mashiba et al, 2001) have revealed that A1AT produced and oxidized by macrophages, attaches to low density lipoprotein (LDL) in the intima of the arterial wall and contributes to the lipid accumulation in arterial wall cells in the early stage of atherogenesis.…”
Section: Oxidation Of A1at -Clinical Aspectsmentioning
confidence: 99%